Pengembangan Media Prezi pada Kemampuan Menulis Teks Cerpen di SMP PKBM Darul Hikam - Sutriyani, Ai; Solihun, Ahmad; wahyudi, wahyudi; Kurniawan, Muh Akbar (Ruang Kata, 2025)
This research aims to develop Prezi-based learning media in improving the ability to write short story texts of grade IX students at SMP PKBM Darulhikam. The research method used is research and development (Research and Development/R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The research subjects consisted of media experts, material experts, and 27 grade IX students. Data collection techniques include interviews, questionnaires, observations, and tests. The results of the study show that Prezi’s media is considered valid with a score of 75% from media experts and 85% from material experts. The trial to students received a positive response with a score of 81%, which was categorized as very feasible. Thus, Prezi media is proven to increase the effectiveness of learning to write short story texts and is suitable for use in learning